Studies on Variability, Character Association and Genetic Diversity in Maintainer Lines of Pearl Millet {Pennisetum glaucum (L.) R. Br.} - Kumari, Neelu; Sharma, N K; Gupta, S K (Annals of Arid Zone, 2018)
Variability, character association and genetic diversity were studied with 150 maintainer lines of pearl millet. Analysis of variance indicated significant variances among genotypes for all 12 quantitative traits studied. Characters like biological yield per plant, flag leaf width, tillers per plant and seed yield per plant showed high PCV along with high genetic advance as per cent of mean. Moderate heritability and GCV indicates the possibility of improving these characters through phenotypic selection. Seed yield had significant and positive correlation with biological yield, tillers per plant, plant height and flag leaf width. The direct and indirect effects of component characters like biological yield per plant, leaves per plant, flag leaf length, flag leaf width, panicle length, panicle diameter, plant height and tillers per plant were found positive on seed yield. Therefore, selection based on these component characters would results in improvement of seed yield also. Based on the D2 analysis all genotypes were grouped into 18 clusters. The contribution of seed yield (27.58%) was found highest towards total divergence followed by biological yield (23.84%), days to maturity (21.20%) and days to flowering (7.36%), respectively. Nineteen genotypes were found superior for seed yield and other related traits in early and medium maturity group of genotypes. Three genotypes namely B-1116, B-1133 and B-1003 were substantially better in both seed yield and biological yield besides other related attributes. Therefore, these genotypes may be used in the breeding program for developing the dual purpose hybrids for arid zone.Key worlds: Correlation, diversity, maintainer lines, pearl millet, quantitative traits, variability.